Pengaruh Efektivitas Kepemimpinan Kepala Sekolah dan Supervisi Pengawas Terhadap Kinerja Sekolah Pada Sekolah Menengah Kejuruan di Kabupaten Ciamis - Andang Rohendi (Peneliti.net, 2020)
This study aims to determine the effect of the effectiveness of principal leadership and supervisory supervision on school performance at Vocational High Schools in Ciamis Regency. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study the effectiveness of the principal's leadership has a significant effect on school performance by 28.1%, hypothesis testing is obtained t count> t table or (6.762> 2.007). Supervisory supervision has a significant effect on school performance by 28.1%, hypothesis testing is obtained t count> t table or (4.505> 2.007). The effectiveness of the principal's leadership and supervisor's supervision simultaneously has a significant effect on school performance with the regression equation Y = 9.913 + 0.484X1 + 0.277X2. The contribution of the effect was 53.3%, the hypothesis test obtained F count> F table or (29.157> 2.790).